Africa's Legacies of Urbanization: Unfolding Saga of a Continent - Goodwin, Stefan (Lexington Books, 2006)
The ability to function safely, healthily, and productively in urban places is a continuing challenge for people everywhere. This challenge is exacerbated when the resources available to people in urban places happen to be severely limited or their ability to make decisions consistent with their welfare severely constrained. Nevertheless, Africans have manifested great inventiveness and resourcefulness both in contributing to, and in adapting to, urbanization. Africa's Legacies of Urbanization is the culmination of several decades of research, travel, and teaching. Goodwin provides an interdisciplinary and up-to-date look at African cities and the urbanization process. This thought provoking and engaging work tackles the vastness of the 'mother continent' by dividing it into geographic regions: western, central, southern, eastern, and northeastern. Beginning with an overview of the urban experience in Africa, Goodwin then studies the histories of urbanization in the various regions of the continent. Thoroughly researched and accessibly written, this comprehensive work will appeal to scholars of African studies, urban studies, anthropology, and cultural ecology.